Współczesne organizacje polonijne i ich rola w życiu Polonii w Holandii - Leska-Ślęzak, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
Starting from the XIX century migrations have become a mass phenomenon. Currently, they are considered a fundamental value and a human right. The Netherlands occupies an important place among the countries to which Poles emigrate. Over the XX and XXI century, the Polish community in the Netherlands established organizational forms which significantly facilitate the Polish emigrees’ living abroad. The Polish diaspora in the Netherlands is estimated at around 200 thous. The contemporary Polonia organizations fulfill many functions: they assist, inform, educate, offer cultural activities. The Internet is the main communication instrument for the contemporary Polish diaspora organizations in the Netherlands.
CONTEMPORARY POLONIA ORGANIZATIONS AND THEIR ROLE IN THE LIFE THE POLISH DIASPORA IN THE NETHERLANDS
Keywords: Poland; the Netherlands; mutual relations